Optimizing System Performance: Load Balancers and High Availability - Vasudevan Senathi Ramdoss (The Eastasouth Journal of Information System and Computer Science, 2023)
Modern computing systems depend on load balancing and high availability to maintain reliability and scalability and achieve optimal performance. Load balancing achieves optimal resource utilization by distributing traffic across several servers to prevent overloading while high availability maintains system operations during maintenance and failure events. The combination of these technologies delivers uninterrupted user experiences and minimizes operational interruptions along with supporting distributed systems expansion. The paper examines fundamental concepts along with practical applications and industry-specific use cases in e-commerce as well as cloud computing and content delivery networks. The study shows how enhanced fault tolerance and system performance improvements come with implementation complexity challenges and increasing security concerns alongside cost considerations.